Правове становище єврейської національної менщини в умовах української державності ( 1917-1920 р.р.) - Кальян, О. С.; Kal'jan, О. (My University, 2010)
The article deals with urgent legal matters of legal status of jewish national community in the conditions of Ukrainian statehood (1917-1920). The author of the article analyzing historical conditions proves that extreme difﬁ culties of political character, social and law life helped to draw together Jewish national community with Ukrainian liberation movement and caused certain changes in the system of law policing of those times.
Кальян О. С. Правове становище єврейської національної менщини в умовах української державності ( 1917-1920 р.р.) / О. С. Кальян // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 545-554.
Keywords: правове становище єврейської меншини в Україні 1917-1920 р. р.; український визвольний рух 1917-1920 р. р.; єврейські національні меншини на Україні; українська державність; украинское освободительное движение 1917-1920 г. г.; еврейские национальные меньшины на Украине; правовое положение еврейских национальных меньшинств на Украине 1917-1920 г. г.; украинская государственность; Ukrainian liberation movement of 1917-1920 was; Jewish National Minorities in Ukraine; the legal status of the Jewish minority in Ukraine, 1917-1920 gg.; Ukrainian statehood